Instrumentos de análisis para identificar operaciones de lavado de dinero - Vera, José Carlos (2006)
Money laundry is the process that hides the origin of resources obtained through illegal activities like drug trafficking, smuggling, corruption, tax fraud, white-collar crimes, public misappropriation, extortion, illegal work, and, lately, terrorism. The resources are presented as coming from legal activities, and are freely traded in the financial system. However, thanks to the ongoing efforts of international organisms, the countries have established regulations, institutions and organisms to fi ght this crime. In Peru, the entity created for this purpose is the Financial Intelligence Unit, and several legal provisions have been set forth in this regard. This document presents a methodology aimed at generating analysis instruments, indicators and procedures to allow fi nancial institutions to detect money laundry operations. The information used to generate said indicators is provided by INEI’s annual economic survey database, and the information to generate the analysis instrument comes from satellite accounts.